Professional development status of teaching staff in a Ugandan public university. Issue 4 (3rd July 2016) - Kasule, George Wilson; Wesselink, Renate; Mulder, Martin
ABSTRACT: A study was conducted to determine general professional development activities perceived to be important in enhancing university teaching staff's job performance, and the extent to which teaching staff participate in these activities in Uganda. Data were collected through semi-structured interviews with faculty deans and department heads ( n  = 20), and a questionnaire administered to university senior administrative staff ( n  = 90) and teaching staff ( n  = 126). Deductive content analysis and descriptive statistics techniques were used to analyse qualitative and quantitative data, respectively. It was established that university teaching staff rarely participate in professional development activities. Nevertheless, activities such as accredited university teacher education and training, symposia, workshops, and professional networks, all oriented on contemporary teaching and learning, research and innovation, and community development activities, are perceived to be important in improving teaching staff job performance. Thus, there is a need to make participation in formal and informal professional development activities mandatory for university teachers.